The Role of E-Learning in the Evolution of Professions: A Moroccan Contextualization (Global Journal of Management and Business Research, 2025)
Abstract not found
Keywords: e-learning; artificial intelligence; higher education; evolution of professions; theory of economic behavior; soft skills; morocco